# Evalute 2x3 - 3x2 + 4x + 5 with x = 4. Dang. Please help. I suck at algebra.

### 12 Answers | Add Yours

Actually, even though I agree with the PEDMAS, However, we tend to use it ina wrong way.

PEDMAS is used to simplify the equations for beginners but the fact is that subtractions and addition have the same priority as well as multiplication and division have the same priority. For example

2*4/5 = ?

lets do the multiplication first

then, 2*4/5 = 8/5 = 1.6

or 2* 0.8 = 1.6 which is the same answer.

so the answer for your question is as follow

2*3 - 3*2 + 4X + 5 =

6 - 6 + 16 + 5 =

6 + (-6) + 16 + 5 = 21 and not -21 because the ( - ) only applies for what comes next ,if there is no parenthesis, which is the 6.

Hope that helps.

Don't suck. Just practice. It's one of these stupid things in math that "x" is used as a variable AND as the multiplication sign. So let's clarify each problem, with "*" meaning multiply:

1a. 2*3 - 3*2 + 4x + 5 where x=4

OK. This is the classic "Which operation do I perform first?" problem. Consider the first part of the equation, 2*3 - 3*2. If you do it in order, you get 6-3, which leaves 3, times 2, which leaves you with 6. This is a trap!! Remember the order of operations: PEMDAS (Parenthesis, Exponents, Multiplication, Division, Addition, Subtraction, done left to right.) The other problem is to keep track of whether the + and - refers to a binary operation (add,subtract) or is the sign (pos,neg) of the integer! So you would clarify the problem by putting parenthesis around the multiplication portions and the negative integers like:

1b. (2*3)-(3*2) + 4x + 5 where x=4 (no neg. integers here)

subsituting 4 for x gives:

1c. (2*3) - (3*2) + (4*4) + 5

so you're left with:

1d. 6 - 6 + 16 + 5

or

1e. 6 - (6 + 16 + 5) (...remember addition before subtraction!)

which gives you:

1f. 6 - 27

1g. -21

You'll be fine. Just keep the order you should do the operations in straight (PEMDAS-Please excuse my dear Aunt Sally, to help you remember; parentheses, exponents, multiplication, division, addition, subtraction) So for the first problem plug in "4" where you have an "X". You get:

2x3 - 3x2 + 4x4 + 5

You only have mult., addition, and subtraction, so....

6-6+16+5, then 6-27, or -21 for an answer.

Good luck, you can do it!

2x3 - 3x2 + 4x + 5 with x = 4

substitute x with 4

2(4)^3 - 3(4)^2 + 4(4) + 5

simplify

2(24) - 3(16) + 16 +5

multiply the numbers inside the parentheses by the numbers outside:

48 - 48 +16 +5

combine

48 -48=0+16=16+5=21

so 21

### Hide Replies ▲

Made a mistake

2(4)^3 - 3(4)^2 + 4(4) + 5

simplify

2(64) - 3(16) + 16 +5

multiply the numbers inside the parentheses by the numbers outside:

128 - 48 +16 +5

combine

128 -48=80+16=96+5=101

so 101

2x3 - 3x2 + 4x + 5 with x = 4.

`2x^3 - 3x^2 +4x + 5 =`

`2 (4^3) - 3(4^2) + 4(4) = `

`(2xx64) - (3xx16) + 14 =`

`128 - 48 + 14 =`

` ` `128 - 48 + 14 + 5 = 101`

``

2x3 - 3x2 + 4x + 5 with x = 4

All you have to do is substitute x with 4

[2(4)^3] - [3(4)^2] +4(4) +5

[2(64)] - [3(16)] + 16 +5

128-48+16+5

128-48+21

128-27

**101 Answer.**

2x3 - 3x2 + 4x + 5 with x = 4.

Since we know what " x " equal , we can plug it into the equation

By plugging it into the equation , you would get

2(4)^3 - 3(4)^2 + 4(4) + 4 ok , now we can start with by raising 4 to the third power .

By raising 4 to the third power , you should get

2 ( 64 ) - 3(4)^2 + 4(4) + 4 Now multiply 2 with 64

By multiplying 2 with 64 , you should get

128 - 3(4)^2 + 4(4) + 4 Now lets raise 4 to the 2nd power

By raising 4 to the 2nd power , you should get

128 - 3 (16 ) + 4(4) + 4 Now we can multiply 3 with 16

By multiplying 3 with 16 , you should get

128 - 48 + 4(4) + 4 We can now multiply 4 with 4

By multiplying 4 with 4 , you should get

128 - 48 + 16 + 4 Now subtract 128 with 48

By subtracting , you should get

80 + 16 + 4 Now add 80 with 16

By adding , you should get

96 + 4 Lastly , we can add 96 with 4

By adding , you should get

= 101 which is your answer

2x3 - 3x2 + 4x + 5 and x = 4

Plug 4 into x and then you solve

2x3 = 6

3x2 = 6

Plug 4 into the x

4(4) which is the same as 4x4 = 16

6 - 6 + 16 + 5

16 + 5

21 is the final answer

2*3-3*2+4x+5. When x=4. So just start step by step. 2*3 is 6

3*2 is 6

4x, in which X is 4 so 4*4 is 16

And then you have 5.

So just subtract first and both 6 end up canceling out. And you're left with 16 + 5. Giving you 21 as your final answer.

2*3-3*2+4(4)+5

6-6+16+5

6-27

-21

(2*3)- (3*2) +4x+5//

Sub. x=4 to equation

6-6+4(4)+5= 0+16+5

= 21//

Substitute x with 4.

2x³-3x²+4x+5

2(4)³-3(4)²+4(4)+5

2(64)-48+16+5

101